Synthesis of dimeric and tetrameric trithiomannoside clusters through convenient photoinitiated thiol-ene click protocol for efficient inhibition of gram-negative bacteria. Issue 1 (31st March 2021) - Mahadevegowda, Surendra H.; Ruan, Lin; Zhang, Jianhua; Hou, Shuai; Raju, Cheerlavancha; Chan-Park, Mary B.
Abstract: Glycoclusters with high glycan density accessible through grouping of monosaccharide units in multimeric forms are important due to their high affinity and capability in recognition with protein receptors as a result of multivalent effect. In this report, we have achieved the assembly of glycoclusters in dimeric to tetrameric forms using efficient light initiated free radical mediated thiol-ene click reaction. Bacterium (UTI89) inhibition study by yeast agglutination assay demonstrated that these multivalent glycoclusters showed more efficient inhibition of bacteria when compared to monovalent sugar units. Graphical Abstract: UF0001